The Use of Exploratory Factor Analysis to Identify Determinants of Green Innovation Product Acceptance Among Generation Z - Maisaroh, Maisaroh; Muslikhah, RR. Siti; Suratman, Andriyastuti; Junianta, Reynaldi Dwi; Sholihah, Masyithoh Annisaush; Saputri, Isna Ajeng; Sofia, Khansa Bunga; Azmi, Afra Nabilah Taqiyyah; Rahma, Nifly Enggina; Rizki, Nur Aisyahnum Miftahul (Journal of Ecohumanism, 2025)
This study aims to identify the factors influencing Gen Z's acceptance of green innovation products in Shuca products, namely perceived value, perceived quality, social influence, green product awareness, and price sensitivity. The method used is a quantitative survey research approach to analyze the determinants of Acceptance of Green Innovation Products, with the Exploratory Factor Analysis (EFA) method employed to determine the number and nature of factors explaining the covariance structure of the data. This research identifies three main factors determining the level of Gen Z's acceptance of green innovation products. First, Perceived Value is a key factor influencing Gen Z's acceptance of green innovation products. Second, Environmental Concern serves as another critical determinant of Gen Z's acceptance of green innovation products. Third, Green Product Awareness significantly affects Gen Z's acceptance of green innovation products. Marketing strategies focusing on quality, perceived benefits, and environmental concern can accelerate market acceptance. Additionally, social and educational campaigns can enhance awareness and preferences for green products. To address price sensitivity, companies need to offer affordable eco-friendly products without compromising quality or sustainability.